Protective effects of extract of Cleistocalyx operculatus flower buds and its isolated major constituent against LPS-induced endotoxic shock by activating the Nrf2/HO-1 pathway. (July 2019) - Tran, Phi-Long; Kim, Okwha; Tran, Huynh Nguyen Khanh; Tran, Manh Hung; Min, Byung-Sun; Hwangbo, Cheol; Lee, Jeong-Hyung
Abstract: The flower buds of Cleistocalyx operculatus are used as an important ingredient in herbal tea and herbal products in several tropical countries. However, their protective effects and underlying mechanisms on lipopolysaccharide (LPS)-induced endotoxic shock remain unclear. The aim of this study was to investigate the anti-inflammatory effects of ethanol extract of C. operculatus flower buds (ECO) and its major constituent 2′, 4′-dihydroxy-6′-methoxy-3′, 5′-dimethylchalcone (DMC) in macrophages and in an experimental LPS-induced sepsis mouse model. ECO inhibited the LPS-induced production and expression of pro-inflammatory mediators in macrophages. In an endotoxic shock mouse model, the oral administration of ECO rescued LPS-induced mortality, and attenuated LPS-induced increases in the serum levels of pro-inflammatory mediators, and damage of the lung and liver tissues. ECO increased the nuclear translocation of the nuclear factor erythroid 2-related factor 2 (Nrf2), as well as the expression of Nrf2 target genes, including heme oxygenase-1 (HO-1), in macrophages. Similar to the effects of ECO, DMC also inhibited the LPS-induced inflammatory response in macrophages and endotoxic shock in mice, and activated the Nrf2/HO-1 pathway. In conclusion, our findings suggested that ECO and its major constituent, DMC, attenuated LPS-induced endotoxic shock by activating the Nrf2/HO-1 pathway. Graphical abstract: Image 1 Highlights: The flower buds of Cleistocalyx operculatus are used as an ingredient in herbal products in several tropical countries. The anti-inflammatory effects of C. operculatus flower buds (ECO) and its major constituent DMC are demonstrated. ECO and DMC attenuates lipopolysaccharide-induced inflammatory response in macrophages and endotoxic shock in mice. The Nrf2/HO-1 pathway is attributable to the anti-inflammatory properties of ECO and DMC in macrophages. The mechanism explains the anti-inflammatory effects of ECO and DMC.